ESTRUTURA GENÉTICO-POPULACIONAL DE Eugenia uniflora L. (MYRTACEAE) EM FRAGMENTOS FLORESTAIS DE MATA ATLÂNTICA - Fagundes, Bruna Saviatto (2013)
The reduction of natural habitats contributes to the lost of biodiversity e to the isolation of the remaining populations. A plant species that has great representativeness in the Atlantic forest is the Eugenia uniflora L., also known as Surinan cherry tree. Intending to investigate the effects of the forest fragmentation in the genetic structure of natural populations of Eugenia uniflora, nine loci SSR and seven loci ISSR were amplified in three Rain Forest fragment populations. The similarity average coefficient between the A, C and D was of 0,31. The genetic similarity among the individuals of the most isolated population (0,42) was bigger than the one found among the populations C (0,34) and D (0,36), which, on the other hand, are connected. The grouping of all the individuals formed three groups corresponding to each studied population. A high genetic diversity was observed among the three populations (FST = 0,34; I = 0,51), and the differentiation was bigger inside the population than among them, corresponding to 71,33% e 28,67% respectively. The genetic diversity average inside the populations (Ho = 0,33; He = 0,47) indicates a deficiency of heterozygotes by the increase of endogamous crossing (Fi = 0,29) and constitutes an answer to the gene flow reduction (Nm = 0,48). According to the grouping of Nei`s genetic distance (1978), population A and D were the most genetically distant. The species genetic variability reduction on these fragmented areas may change the E. uniflora adaptive capacity to environmental changes and interfere with the community dynamic of associated species.